What is responsible management of private rangeland? - Rolston, Holmes, 1932-2025, author; Texas A&M University, Texas Agricultural Extension Service, publisher (Colorado State University. Libraries, 1995)
The rangeland manager should examine not just this or that forty acres, or four thousand acres of private land. One is managing in the context of landscape wide ecosystems. Do you want to manage nature? Or do you seek an increased quality of life in habitat? Nature in that sense is not a resource to be managed, but a home where we reside. Dealing with an acre or two of real estate, perhaps even with hundreds or thousands of acres, we can think that the earth belongs to us, as private property holders. Dealing with a landscape, we can think that the earth belongs to us, as citizens of the country geographically located there. But even on landscape scales we pass from a sense of what belongs to us to a sense of belonging in a place.
Proceedings from a conference of the Texas Section of the Society for Range Management.
Keywords: sense of place; residence on landscapes; range management; natural resources; ecosystems